Jesuit Guide to (Almost) Everything, The A Spirituality for Real Life - James Martin (HarperCollins, 2011)
St. Ignatius Loyola (1491-1556), the founder of the Society of Jesus (aka the Jesuits), was known for his practical spirituality. The "way of Ignatius" has helped millions of people-from the doubtful seeker to the devout believer-find freedom, make friends, live simply, work sensibly, fall in love, experience joy, and enter into a relationship with God. The Ignatian goal of "finding God in all things" eans that every part of our lives can lead us to God. The Jesuit Guide to (Almost) Everything shows us how this is possible, with user-friendly examples, humorous stories and anecdotes from the heroic and inspiring lives of Jesuit saints and average priests and brothers, as well as examples from Martin's twenty years as a Jesuit. The traditional wisdom that Jesuits use to help other people in their daily lives is easily applied, but not often explained well to the general public. The Jesuit Guide to (Almost) Everything translates these insights of St. Ignatius for a modern audience and reveals how we can find God-and how God can find us-in the real world of work, love, suffering, decisions, prayer, and friendship.